2020
DOI: 10.33448/rsd-v9i10.8102
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do potencial evocado auditivo P300 antes e após o treinamento auditivo acusticamente controlado

Abstract: Objetivo: avaliar os resultados do potencial P300 em indivíduos com diagnóstico de Transtorno do Processamento Aditivo Central, antes e após o Treinamento Auditivo Acusticamente Controlado. Métodos: Estudo tipo observacional, descritivo e longitudinal. Participaram do estudo cinco crianças de oito a 14 anos de idade. Foi realizada a avaliação e reavaliação do processamento auditivo central e P300 antes e após a aplicação do programa de Treinamento Auditivo Acusticamente Controlado. Resultados: Foi realizada an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…In a study, the cognitive potential -P300, which is a cognitive auditory potential, showed considerable change, both in latency and amplitude, showing the effect of neuroplasticity after the intervention (29) . When analyzing the effectiveness of auditory training through the P300, the authors found reduced latency and increased P300 amplitude after the intervention, results that are consistent with the findings of the current study.…”
Section: Discussionmentioning
confidence: 98%
“…In a study, the cognitive potential -P300, which is a cognitive auditory potential, showed considerable change, both in latency and amplitude, showing the effect of neuroplasticity after the intervention (29) . When analyzing the effectiveness of auditory training through the P300, the authors found reduced latency and increased P300 amplitude after the intervention, results that are consistent with the findings of the current study.…”
Section: Discussionmentioning
confidence: 98%
“…Em um estudo, o potencial cognitivo -P300, que é um potencial auditivo cognitivo, apresentou considerável mudança, tanto em latência, quanto em amplitude, demonstrando o efeito da neuroplasticidade após a intervenção (29) . Ao analisarem a efetividade do treinamento auditivo por meio do P300, os autores observaram redução da latência e aumento da amplitude do P300 após a intervenção, resultados condizentes com os achados do atual estudo.…”
Section: Discussionunclassified
“…There are several previous studies in the literature involving the AP and the AEPs, especially regarding the P300 cognitive component. 11,[14][15][16] Additionally, there are studies that sought to investigate the electrophysiological activity of the central auditory pathway in cases of APD, correlating the objective findings with the behavioral ones. 17,18 However, there are no in-depth studies on the accuracy of AEPs in AP alterations in adults, without other associated pathologies.…”
Section: Introductionmentioning
confidence: 99%